2007
DOI: 10.1007/s10734-007-9074-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personal networks and social support on study attainment of students in university education

Abstract: In this paper, the influence of personal networks and social support on study attainment of students in university education is examined. Furthermore, the paper aimed at clarifying the possible mediating role of achievement motivation, time spent on studying and working, procrastination and self-esteem. The study is a follow-up of the '89 cohort study, but is restricted to those students who have transferred to university education after finishing secondary education. The students have been approached with a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 58 publications
2
49
0
1
Order By: Relevance
“…However, the negative impact of social activity (odds ratios smaller than 1) does not imply that social contacts are per se a threat to being successful at university. It has been shown that a social network can certainly be beneficial for students in completing their study successfully (Eggens, van der Werf, & Bosker, 2008). The impact of extraversion seems further to depend on the selected prediction criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, the negative impact of social activity (odds ratios smaller than 1) does not imply that social contacts are per se a threat to being successful at university. It has been shown that a social network can certainly be beneficial for students in completing their study successfully (Eggens, van der Werf, & Bosker, 2008). The impact of extraversion seems further to depend on the selected prediction criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Eggens, van der Werf, and Bosker (2007) note that personal networks affect student attainment, and Clifton et al (2004) observe how peers give an individual the sense of coping and hence perceived control over academic progress. Harvey, Drew, and Smith (2006) noted how students from lower-income families have less peer support to draw on, and go on to suggest that there is some correlation between socio-economic groups, first-year grades and the possibility of withdrawing from study (especially where family problems intervene).…”
Section: Introductionmentioning
confidence: 99%
“…An online community also gives participants a sense of belonging, provides easy access to other participants and prevents the feeling of isolation participants might experience [1][2][3], thus reducing the chance of participants dropping out [4][5][6]. However, since community formation is a dynamic process, it is inherently unpredictable [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Social capital represents the participant's relationships within a social network, as well as the mutual support between participants [12]. The features of social capital include: (1) the social structure of the network -how are participants connected - [2,13], (2) the sense of belonging to the community [6,[14][15][16], and (3) the social support received and provided [17].…”
Section: Introductionmentioning
confidence: 99%